Construção, avaliação da imunogenicidade e potencial protetor em modelo murino, de diferentes construções do Vaccinia virus Ankara modificado (MVA) expressando a proteína E de Dengue virus sorotipo 3 - Barbara Resende Quinan (2014)
Dengue is, currently, the most important human disease caused by an arbovirus. Dengue virus (DENV) has four serotypes (DENV 1-4) and is estimated to be responsible for 390 million infections per year worldwide, in which at least 2 million result in severe forms of the disease, Dengue hemorrhagic fever and Dengue shock syndrome (DHF/DSS). Despite the high number of cases per year and the fact that approximately half of the world's population are at risk of for dengue, effective drugs for the disease treatment and vaccines are still not available. Among different strategies used for vaccine development, vectors based on recombinant Vaccinia Ankara Modified virus (MVA) shows promise in a number of settings. Thus, in this work, several recombinants of MVA were constructed, all expressing the E protein of DENV-3, but with different elements inserted at the ends of the foreign gene. The ultimate aim was to test which of these modifications would make the most immunogenic vaccine. To enable CD8+ T cell responses evaluation, two epitopes in the DENV-3 E protein in C57BL/6 mice were identified and described. Thus, the evaluation of CD8+ T cell responses in mice immunized with the different recombinant viruses demonstrated that recombinant MVA viruses holding the natural signal peptide of the E protein and, therefore, addressing this protein into the endoplasmic reticulum, have a better response. Evaluations of the humoral response have also shown that these viruses containing this signal sequence are able to stimulate a robust production of anti-E antibodies, while the virus without the signal peptide does not induce any production of antibodies. Furthermore, analyses of protection in C57BL/6 mice suggest that immunization with this more immunogenic construct is protective. Thus, these results demonstrate the importance of this signal peptide sequence and, in the future, this more immunogenic construction could be used for construction of recombinant MVA to other DENV serotypes. Ultimately these could be combined to make a tetravalent DENV vaccine.